Effectiveness of banana peels and papaya seeds as alternative coagulants in water treatment - Nur Syahira Syamimi, Razali; Noor Hasyimah, Rosman; Inawati, Othman; Hasnida, Harun3 (AIP Publishing, 2024)
Abstract. The use of natural coagulant as an alternative coagulant, compared to chemical coagulant are due to environmentally friendly, readily available, cost effective and easy to find in the community. Banana peels and papaya seeds are usually considered as waste which these wastes are maybe useful in improving the quality of river water. Therefore, this study aims to evaluate the effectiveness of banana peels and papaya seeds for river water turbidity removal in which Sungai Langat was used as water sample. Using a simple synthesis process, a natural coagulant derived from banana peels and papaya seeds was created in a powder form. The pH, coagulant dosage, and extraction solvent are the variables that varied in the jar test experiment and based on the decrease in turbidity, the effectiveness of natural coagulants was evaluated. The treatment of river water using banana peels coagulant was found to be most effective at pH 4 while papaya seeds at pH 12, with the optimum dose of both coagulants was 180 mg/L. Banana peel coagulant recorded the highest removal percentage of 95.76 % from the initial turbidity of 107 NTU. Meanwhile, the removal percentage of papaya seed coagulant was 94.35 % from the initial turbidity of 110 NTU. A comparison of the use of this alternative coagulant was made with aluminium sulphate (alum). Alum recorded a lower turbidity removal percentage which was 75.66 % at pH 12. The most effective solvent to synthesis banana peels and papaya seeds was sodium hydroxide (NaOH) with a concentration of 2 M. Results showed the possibility and effectiveness of using alternative coagulant in the water treatment process and both natural coagulants (i.e., banana peels and papaya seeds) can enhance the coagulation activity as a green modification approach.